2023
DOI: 10.1101/2023.01.10.22283706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The community as an active part in the implementation of interventions for the prevention and control of tuberculosis: a scoping review

Abstract: Interventions involving direct community stakeholders include a variety of approaches in which members take an active role in improving their health. We evaluated studies in which the community has actively participated to strengthen tuberculosis prevention and control programs. A literature search was performed in Pubmed, Scopus, ERIC, Global Index Medicus, Scielo, Cochrane Library, LILACS, Google Scholar, speciality journals, and other bibliographic references. The primary question for this review was: what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…These community partners can be community health centers, public health departments, schools, prisons, and civil society organizations such as neighborhood organizations [14,47,48]. A case of collaborative association with a CBPR approach is a study that we carried out on the population affected by TB in Peru in collaboration between the Universidad Peruana Cayetano Heredia, Ohio State University, and the Association of Tuberculosis Patients of Comas [ASET] (Comas, district of Peru with a high rate of tuberculosis) [49]. In the first phase, we conducted an empowerment program for CHW in ASET through research training, and in the second phase, we implemented an intervention led by CHW to assess the effect of social determinants of health in tuberculosis in the population affected by TB.…”
Section: Discussionmentioning
confidence: 99%
“…These community partners can be community health centers, public health departments, schools, prisons, and civil society organizations such as neighborhood organizations [14,47,48]. A case of collaborative association with a CBPR approach is a study that we carried out on the population affected by TB in Peru in collaboration between the Universidad Peruana Cayetano Heredia, Ohio State University, and the Association of Tuberculosis Patients of Comas [ASET] (Comas, district of Peru with a high rate of tuberculosis) [49]. In the first phase, we conducted an empowerment program for CHW in ASET through research training, and in the second phase, we implemented an intervention led by CHW to assess the effect of social determinants of health in tuberculosis in the population affected by TB.…”
Section: Discussionmentioning
confidence: 99%
“…C havez- R imache et al . [ 28 ] also reported the significant impact of active community participation in strengthening TB prevention and care programmes, highlighting the necessity of departing from traditional scientific research approaches dominated by academic researchers and embracing a comprehensive and ecological framework that incorporates the community and other social actors.…”
Section: The Road Towards a Neutral And Inclusive Tb Languagementioning
confidence: 99%
“…Pairing community-based interventions with existing healthcare infrastructure and/or programmes appears vital for active case finding and treatment continuation, as the involvement of influential community and family members acts as a facilitator of trust for treatment engagement while providing mechanisms for closer supervision and thus maximising adherence [27]. CHAVEZ-RIMACHE et al [28] also reported the significant impact of active community participation in strengthening TB prevention and care programmes, highlighting the necessity of departing from traditional scientific research approaches dominated by academic researchers and embracing a comprehensive and ecological framework that incorporates the community and other social actors.…”
Section: "Key and Vulnerable Populations"mentioning
confidence: 99%